2014
DOI: 10.1583/13-4410mr.1
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Endovascular Therapy for Aortoiliac Bifurcation Lesions in the Real-AI Registry

Abstract: Stenting for aortoiliac bifurcation lesions was found to be safe and effective. Neither stent configuration nor type appeared to affect vessel patency in true bifurcation lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 37 publications
1
26
1
1
Order By: Relevance
“…Recently, Dohi et al reported a favorable secondary patency rate (94% at three years) after EVT for AIOD in Japanese patients (8). Furthermore, Aihara et al demonstrated feasible primary patency rates (87% at one year and 73% at five years) in Japanese patients with aorto-iliac bifurcation lesions included in the real-AI registry (9). These data indicate that EVT may have the potential to achieve patency rates surpassing those of bypass surgery (3).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Dohi et al reported a favorable secondary patency rate (94% at three years) after EVT for AIOD in Japanese patients (8). Furthermore, Aihara et al demonstrated feasible primary patency rates (87% at one year and 73% at five years) in Japanese patients with aorto-iliac bifurcation lesions included in the real-AI registry (9). These data indicate that EVT may have the potential to achieve patency rates surpassing those of bypass surgery (3).…”
Section: Discussionmentioning
confidence: 99%
“…During the period of May 2014 until May 2016, patients who came to the vascular clinic of Sina hospital with chronic lower limb ischemia signs in terms of Rutherford classification (10) of grade I or higher and absence of femoral pulses bilaterally, were screened with multi-slice CT angiography and all of those with total infra-renal bilateral aortoiliac occlusion (a sub category TASC II type D) were brought into the study. Patients were categorized according to Rutherford classification (10). Patients with intermittent claudication were first treated with exercise therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Aihara et al reported an 87% patency rate for one year of follow-up that shows no significant difference with our result, although the complication rate in their study was 6.3%. Moreover, their patients suffered from different types of lesions with a dominancy of TASC II C and D, which can lead to better results due to complexity of type D lesions (10). Another study conducted by Shen et al demonstrated a 93.6% patency rate for one-year post-endovascular therapy (11).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Endovascular treatment has become a major part of revascularization of iliac artery occlusive disease [19][20][21]. Among the various interventional devices, stent is main stay of treatment strategy.…”
Section: Iliac Artery Disease: Tasc Ll A-cmentioning
confidence: 99%